Binary Image Denoising via Incremental Neighborhood-Based Energy Optimization: A Markov Random Field Approach - Martinez, Victor José Beltrão Almajano; Clímaco, Francisco Glaubos Nunes; Silva, Aristófanes Corrêa (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI), 2025)
A digital image may exhibit undesired noise variations, making it necessary to apply preprocessing methods to reduce noise while preserving the original structure. In this context, this paper proposed a Markov random field-inspired energy approach for optimizing binary noise reduction, considering a variable neighborhood set. Our algorithm combines Iterated Conditional Modes with Markovian prior information about the image to compute the energy associated with each pixel based on its local neighborhood, which is progressively expanded at each iteration. Experimental results on binary images corrupted with 10% random noise demonstrate that the proposed approach achieves an agreement of up to 99.85% with the original noisefree images. Future research will focus on incorporating more prior knowledge about the image to enhance the energy model, as well as its extension to grayscale images, along with the exploration of new metrics and configuration strategies.